GAMES: THE WAY AFFECTS ADULTS' COGNITIVE AND AFFECTIVE SKILLS IN LEARNING - Sonyel, Bengi; Muradzikwa, Munashe; Shublaq, Marwan; Canay, Asena (Iated-Int Assoc Technology Education & Development, 2018)
The purpose of this study is to provide introduction on the role of computer games in classroom environment, evaluate the effectiveness of learning from computer games and the general effects of games. There is a variety of games such as action games, adventure games, fighting games, knowledge games, simulation games, management and strategy games, drill-and-practice games, logical games and mathematics games (Kaptelinin and Cole 2001). Game play can be competitive, cooperative or individualistic (Becta, 2002). Video games are a modern phenomenon. According to Fabricatore (2000), there are two key elements which distinguish video games. These are: 'Videogames always include an interactive virtual playing environment' and 'In videogames the player always has to struggle against some kind of opposition. The study investigates the potential of game-based learning according to the students' perspectives and also the views of students on various factors considering educational games.
12th International Technology, Education and Development Conference (INTED) -- MAR 05-07, 2018 -- Valencia, SPAIN
Keywords: Gaming; Educational Games; Game Based Learning; Gamification; Simulation